Risiko dan pulangan dalam sukuk: Kajian di pasaran modal Indonesia / Eka Nuraini Rachmawati - Eka Nuraini , Rachmawati (2017)
Risks and returns are important for investors, as they expect high returns with low risk. However, in practice the financial instruments take the high risk high return method, which means the higher the risk of higher returns, the less risk it becomes, the smaller the returns the investor receives. In jurisprudence is known as al ghurm bi al ghunm. Investors who purchase financial instruments can choose financial instruments that generate high returns but the risks are high or choose a monetary policy that lowers risk but low returns are also low. The purpose of this study is to prove whether Islamic securities have the same characteristics as conventional securities, following the high risk high return method or al ghurm bi al ghunm. That means, the higher the risk will be the higher returns that investors will receive. This study examined whether high risk sukuk will result in high returns and sukuk that have low risk and vice versa. This study was conducted in two stages of analysis, first, comparing the risks and returns between Ijārah sukuk and Muḍārabah sukuk. The second step, measured the impact of some sukuk and coupon risks on sukuk returns using yiled to maturity (YTM). The population of this study is the entire sukuk issued in the Capital Market of Indonesia, while the sample is the Sukuk Mudahrabah and Ijārah which is still circulating from 2010 to 2014. Data analysis used independent sample t test and multiple regression ratios. The findings show that the Muḍārabah sukuk risk and returns are greater than sukuk Ijārah. However, based on independentt test analysis, the returns and risks of both sukuk are not significantly different. Regression results are found that affecting sukuk returns are interest rate risk, maturity, coupon rate and rating. Concurrently, the effect of interest rate, maturity, coupon rate and rating risk on the rate of return of 44%. That means, the 44% sukuk return is influenced by the interest rate of the Bank Indonesia Certificate (SBI), maturity, coupon rate and sukuk rating. SBI interest rates, maturities have positive effects on returns, but coupons and ratings have a negative effect on returns. The conclusion of this study is that the returns and risks of Ijārah sukuk and Sukuk Muḍārabah are not significantly different, so it is desirable if a company is more interested in issuing Ijārah sukuk and investors are more likely to buy sukuk Ijārah because of its low risk. The Ijārah sukuk provide constant returns while Muḍārabah's sukuk return fluctuates depending on the company's earnings. It can be concluded that the high risk high return or al ghurm bi al ghunm method of Islamic financial instruments, especially in corporate sukuk issued in the Indonesian Capital Market, does not occur, as is the case with conventional financial instruments